A Case Study on Teacher’s Challenges on Inclusive Mathematics Classes in a Secondary Public School - Juan Paolo Martin Culajara; Carla Jobelle Culajara (Journal of Mathematics Instruction, Social Research and Opinion, 2023)
Inclusive education became the mainstream educational system in the Philippines. The study used a qualitative research design employing a case study approach. Two Mathematics teachers were observed and interviewed. Purposive sampling was used to choose the participants. Data gathering is carried out through open-ended questions, interviews, and observation. Three themes emerged in the study: lack of ASL training, personalization in pedagogy, and upskilling teachers’ competency in inclusive education. This study reveals that learning should not be constrained and can be attained when everyone collaborates. It was evident that teaching is a continuous process that should not be interrupted because teaching is the noblest profession. Teachers and administrators should offer programs, projects, and activities connected to pedagogy, addressing diversity and personalizing in providing excellent services since inclusive education is now available within the educational system. It is recommended in the study to strengthen and expand inclusive education so that each student can be given more priority in accessing education for all, give them more possibilities and opportunities to address their differences, and strengthen their inherent capabilities as valuable members of society. The study seeks to contribute to the existing body of knowledge on inclusive education by exploring the experiences and perspectives of educators in the field.